اتجاهات الباحثين نحو قضايا التعليم العالي في الجمهورية اليمنية - الخطيب، خليل محمد مطهر (جامعة العلوم والتكنولوجيا, 2022)
هدفت الدراسة إلى تحليل اتجاهات الباحثين نحو قضايا التعليم العالي في الجمهورية اليمنية، واعتمدت الدراسة على المنهج الوصفي، وتمت عملية تحليل البيانات بطريقتين هما: التحليل الكمي، والتحليل النوعي، وتوصلت الدراسة إلى جملة من النتائج، أهمها: أن عدد الرسائل المتعلقة بالتعليم العالي (759) رسالة، منها (67%) للذكور، و(33%) للإناث، و(72%) ماجستير، و(28%) دكتوراه، وبلغ الإنتاج العلمي ذروته عام 2014 م، وحصلت اللغة العربية على المرتبة الأولى بنسبة (90%)، واليمن أولا كبلد الدراسة، وبنسبة (80%)، وحصلت جامعة صنعاء على المرتبة الأولى بنسبة (42%)، أما اتجاهات الباحثين فتوزعت على (25) مجالا، وحصلت مجالات: السلطة والقيادة والإدارة والحوكمة، والجودة والاعتماد الأكاديمي، وتكنولوجيا التعليم على المراتب الثلاث الأولى على التوالي، وبنسبة مجتمعة (53%)، وبقية النسبة لبقية المجالات، وفي ضوء النتائج قدمت الدراسة عددا من التوصيات والمقترحات. The study aimed to analyzing researchers’ attitudes towards higher education issues in Yemen. The study followed the descriptive approach. Data analysis was done by quantitative analysis and by qualitative analysis. The study reached a number of results, the most significant of which are the following :The number of the theses and dissertations related to higher education is (759), distributed as (67%) males and (33%) females, and as (72%) M.A. theses and (28%) Ph.D. dissertations. In addition, scientific productivity reached the highest level in 2014. Arabic language came first scoring (90%). Yemen as the country of such studies came first with a percent of (80%). Sana’a University came first with a percent of (42%). Moreover, researchers’ attitudes were distributed into (25) fields. Fields of “authority, leadership, administration, governance”, “quality and academic accreditation”, and ‘education technology came in the first three ranks respectively, with a percent of (53%) for such fields. The other fields scored (47%). In light of the results, the study offered some related recommendations and suggestions.
Keywords: الإدارة التربوية -- التعليم الجامعي -- التنمية التعليمية -- البحث العلمي -- اليمن